Challenges in application of the " responsibility to protect" as a norm in the international community's response to the humanitarian impasse : Rwanda and Darfur - Stemmet, Pieter Andreas (University of Pretoria, 2013)
Mini Dissertation (LLM (International Law))--University of Pretoria, 2010.